A Time-Saving and Plasma-Saving Method for Determination of Glycyrrhetic Acid in Human Plasma by HPLC-MS/MS - Zhai, Y.Y.; Xu, Y.; Luo, Y.N.; Wang, X.J.; Guo, Q.X. (Asian Journal of Chemistry, 2012)
A sensitive, time-saving and plasma-saving HPLC-MS/MS method was established and validated for the quantification of glycyrrhetic acid in human plasma using oleanolic acid as the internal standard. Dichloromethane as the organic solvent was used to extract the glycyrrhetic acid and internal standard from 100 μL plasma. After liquid-liquid extraction, the post-treatment samples were analyzed on a Luna CN column interfaced with HPLC-MS/MS in negative selected reaction monitoring mode. The mobile phase was composed of acetonitrile and water (containing 0.05 % acetic acid and 0.02 % ammonium acetate) (95:5 v/v) at a flow-rate of 0.2 mL/min throughout the experiment. The linearity ranged from 2.5 to 160 ng/mL and the correlation coefficients for the calibration curves ranged from 0.998 to 1.000. More than 500 plasma samples were prepared and analyzed within 2 days. This method was successfully employed in pharmacokinetic study after oral administration of 150 mg glycyrrhetic acid to 19 healthy volunteers.